Product shape and trade dress protection under trademark law in Europe - LLEWELYN, Gordon Ionwy David (Institutional Knowledge at Singapore Management University, 2001)
Trade dress, an American term perhaps better-known in British English as 'get-up', is a distinctive, non-functional feature which distinguishes a trader or manufacturer's goods or services from those of others. It may consist of inter alia colour, shape, design, sound, smell, product packaging or product configuration. One might describe trade dress as encompassing the total image and overall impression created by a product. In Europe protection afforded to features falling outside established trademark laws has traditionally been under laws of unfair competition or unfair marketing practices (in the United Kingdom, under the law of passing-off). However, in 1988 the European Community adopted the First Trademark Directive (the "Trademark Directive" or the "Directive"),' which expanded, at least for some Member States, the notion of what could be protected by trademark.